A Case Report of Madelung's Disease - Lee, Bo Hyun; Lee, Young Mann; Park, Seong Oh; Chang, Lan Sook; Kim, Youn Hawn (Archives of Plastic Surgery, 2023)
Madelung's disease (MD) is a rare disease characterized by diffuse, nonencapsulated, multiple fat masses in different areas of the body. In this case report, we present a case of MD in Asia and its management. A 66-year-old man with a history of hypertension presented with massive growth of soft tissue around the neck, breasts, upper back, and lower abdomen. Preoperative magnetic resonance imaging revealed remarkably hypertrophic fat tissue around the neck and anterior chest was wall, which consistent with the diagnosis of MD. Multiple linear incisions were made on the neck and 763, 186, 635 g of posterior, right, and left fat tissues were excised, respectively. A single wide, transverse incision was done to excise 1,072 g of fat from the upper back. Masses of both breasts were excised, preserving the inferior pedicle, weighing 1,086 (right) and 1,164 g (left). The recovery was optimal and the patient was discharged without complications. In this case, we excised the adipose masses as much as possible and improved contour and symmetry. However, the fat infiltrations in the patient were diffusely distributed, making total fat excision difficult. This rare case report may help in managing patients with MD.
Keywords: lipoma; lipomatosis; Madelung's disease; case reports